Learn more Python the hard way workshop - Shaw, Zed; Safari eBooks ([Indianapolis, Ind.?] : Pearson : Addison-Wesley, 2015)
"This video shows beginners who know basic Python and shows them how to take a concept or idea and turn it into a working piece of software. The projects are small enough for you to complete in one to three hours each, on your own, after watching Zed do it. Each project will include a list of similar projects you can complete on your own and extra challenges to further your education."--Resource description page.
Presenter, Zed Shaw
Title from title screen (viewed January 5, 2015).
Keywords: Python (Computer program language); Electronic books